Comparison of the efficacy of 70% ethyl alcohol solution and ethyl alcohol-based hand gel in hand antisepsis - Montegrejo, Aristotle M.; Mendoza, Michael Antonio F., (Faculty co-author).; Gener-Estibaya, Rosa Maria Wilhelmina D., (Faculty co-author).
Objective: To compare the efficacy of 70% ethyl alcohol solution and ethyl alcohol-based hand gel in reducing the level of microorganisms on contaminated hands.
Methods: Data collection using the glove juice technique was done on three meetings with a one week interval with two groups of participants of UP College of Dentistry students (n=40). Both groups tested both alcohol-based agents to decrease bias: Group A testing the alcohol solution and Group B testing the alcohol gel on the second meeting. On the third meeting, Group A tested the alcohol gel and Group B tested the alcohol solution. The number of colony forming units (CFUs) in blood-agar plates after the use of each alcohol-based agent was compared to the baseline data, and between the two alcohol-based agents.
Results: Outlying data were present due to possible experimental errors. These data had significantly higher CFU count after the use of the alcohol-based agents compared to the baseline data. Outliers that are clearly the result of spurious activity should be removed (Cousinea and Chartier, 2010). Excluding the outliers resulted in a statistically significant decrease in microbial load for both alcohol solution and alcohol-based hand gel, in comparison to the baseline number of CFUs. On the other hand, results also show that with or without the outlying data, the difference between the number of CFUs after alcohol solution use and the number of CFUs after alcohol gel use is not statistically significant.
Conclusion: The difference between the efficacy of 70% ethyl alcohol solution and ethyl alcohol-based hand gel is not statistically significant.
Keywords: efficacy, ethyl alcohol-based hand gel, 70% ethyl alcohol, hand antisepsis
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Asepsis and antisepsis; Alcohol; Hand gel